Source-to-sink system and sedimentary characteristics of the lower Miocene submarine fans in the eastern deepwater area of the Qiongdongnan Basin, northern South China Sea - Sun, Rui; Yao, Xingzong; Wang, Xiayang; Wu, Keqiang; Han, Yinxue; Xu, Jianyong; Yang, Haizhang; Li, Hongyi; Zeng, Qingbo; Song, Zezhang (Frontiers in Earth Science, 2022)
The submarine fan results from the sediments transported by gravity flow from the shelf-upper slope to the abyssal plain, which records the regional paleoclimate, paleoenvironment, tectonic movement, the information on relative sea-level change but also stores a vast amount of oil and gas resources. Based on a large number of newly collected 3D seismic data, drilling data, heavy minerals and rare earth elements(REE) data, this paper analyzes the characteristics of the source-channel-sink of the submarine fan system in the Early Miocene in the Songnan-Baodao-Changchang Sag of the Qiongdongnan Basin in the northern South China Sea. The study shows that the bulge area developed in the north and south sides of the Songnan-Baodao-Changchang Sag in the Qiongdongnan Basin due to the control of tectonic-paleo-morphology during the Early Miocene, and the southern part of sag is a small provenance which near-concave uplift; the provenance area in the northern part of sag is large, but provenance direction is different, which forms different provenance systems. During the early Miocene, a series of canyon systems in the Songnan-Baodao-Changchang sag of the Qiongdongnan Basin were the primary channels for sediment transport from shallow water shelves to deep-water slope. During the early period of the Early Miocene, the size of the canyon was generally more prominent due to the regional sea level decline, and the size of the canyon on the northern margin of the Songnan Sag was significantly more extensive than that of the Baodao Sag; During the late period of Early Miocene, the size of the canyon is small, narrow and shallow with the rise of relative sea level. Under the dual control of the "source-channel" system, the multiple delta-canyon-submarine fan sedimentary systems developed in the Songnan-Baodao-Changchang Sag of the Qiongdongnan Basin. The large deltas were distributed along the northern part of the sag and were deposited to the edge of the shelf of the Songnan-Baodao-Changchang Sag from north to south, which provides a good material basis for the development of deep-water sediments.